PENYINGKAPAN-DIRI, PERILAKU SEKSUAL, DAN PENYALAHGUNAAN NARKOBA - Agnes Dewanti Purnomowardani; - Koentjoro (Jurnal Psikologi, 2000)
Research was based on drug abused phenomenon of youth, which lead to the question: what the real caused and the effect of drug abuse was. The aim of the research was to find out whether there were correlation between self-disclosure and drug abuse, the drug abuse and sexual behavior, and the self-disclosure and sexual behavior. Here also to answer empirical research about why the interrelation between 3 variables above was existed and how those effect to one another. Subjects were 18-24 years old drug users in Yogyakarta and already graduated from or still in High School. Fifty-one subjects successfully participate this research. Researcher was using Quantitative Method for analyzing data, Product Moment Analysis and Regression Analysis, and Qualitative Method for answering empirical question about the psychological dynamics of drug abusers. The research was proceed by giving Self-Disclosure Questionnaire and Sexual Behavior Questionnaire to all subjects. Followed by In Depth Interview, Participant Observation, and finally Focus Group Discussion was conducted to 3 of them in order to have a comprehensive understanding about drug abusers. The result of quantitative data analysis shows there are no correlation between either sels-disclosure and drug abuse nor drug abuse and sexual behavior. Nevertheless, there is a significance correlation between selfdisclosure and sexual behavior. The result of qualitative data shows some substance dealing with drug abusers. The substances are the the first drug used started from trial and error, the effect of drugs abused to sexual behavior depend on each individual differences, and the users show unsatisfied relationships to their parents but has a high level of self-disclosure especially to the peer from the same sex. Keywords: self-disclosure, sexual behavior, and drug abuse